2018
DOI: 10.1002/jbt.22280
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction and antiproliferative effect of a novel curcumin derivative MOMI‐1 on the human lung cancer cells A549

Abstract: To date, there are some chemically synthesized curcumin derivatives which were produced and identified to evade the disadvantages of physiochemical stability and solubility of curcumin. Here, one novel curcumin derivative, (2‐(3‐{(1E)‐{(E)‐3‐(4‐hydroxy‐3‐methoxybenzylidene)‐2‐oxocyclohexylidene)methyl)‐1H‐indol‐1‐yl)acetic acid}, (abbreviated as MOMI‐1) was first used to detect the antiproliferation activity with MTT assays in different cancer cells including A549 lung cancer cells, MCF‐7, and HEPG2 cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Autophagy is an essential contributor to multiple physiological and pathophysiological reactions, such as cellular viability and apoptosis (28,29). Emerging evidence has suggested that autophagy is essential for malignant progression (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an essential contributor to multiple physiological and pathophysiological reactions, such as cellular viability and apoptosis (28,29). Emerging evidence has suggested that autophagy is essential for malignant progression (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…For example, autophagic death had been identified as a common way for chemotherapeutic drugs or molecules to inhibit or kill tumor cells in recent studies. [19][20][21] In this study, a novel synthetic chemically curcumin derivative, ZYX02-Na (Figure 1), was used to inhibit the proliferation and migration of human non-small cell lung cancer (NSCLC) cells A549.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy necessitates the formation of a double-membrane organelle termed autophagosome that ensures the capture and the transport of their contents to the acidic lysosome [ 36 ]. Acridine orange (AO) is a weak base fluorophore that accumulates in a protonated form inside acidic vesicular organelles such as lysosome [ 37 ]. In this study, A549 cells were treated with or without Ple-a at a concentration of 42 μM (IC 50 ) for 48 h, and then stained with AO for 15 min, and the appearance of acidic vesicles was observed under a fluorescence microscope.…”
Section: Resultsmentioning
confidence: 99%